Comparison of Nd: YAG (Neodymium-Doped Yttrium Aluminum Garnet) Laser Posterior Capsulotomy Techniques in The Treatment of Posterior Capsular Opacification - Parveen, Shagufta; Naeem, Saquib; Hanif, Kashif; Akbar, Bushra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the safety and efficacy of different techniques of neodymium: yttrium-aluminum-garnet (Nd: YAG) laser posterior capsulotomy.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital Nowshera, from Aug 2015 to Mar 2017.Methodology: A total of 120 patients fulfilling the inclusion criteria were allocated to three groups. Group-A (Circular-group, CG) patients were subjected to circular pattern capsulotomy, group-B (Hinged-group, HG) patients underwent hinged pattern capsulotomy and group-C (Modified-group, MG) had a circular pattern of Nd: YAG posterior capsulotomy along with vitreous strand cutting (modified round pattern). Primary outcome measures were the best-corrected visual acuity (BCVA), intraocular pressure (IOP) and annoying floaters at three-months follow up visits.Results: The mean age of patients was 52.27 ± 5.65 years and there were 64 (53.3%) males and 56 (46.7%) females. The bestcorrected visual acuity improved significantly (p